(untitled) (Indonesian Journal Of Social Issues and Multidisiplinary Studies, 2026)
The North Natuna Sea is a strategic area facing threats of sovereignty violations, illegal fishing, and regional geopolitical dynamics that have the potential to disrupt national stability. These conditions require strengthening operational cooperation and information exchange between the Indonesian National Armed Forces (TNI) and maritime stakeholders to ensure effective maritime security. This study aims to analyze the actual conditions of operational cooperation, identify factors that influence success, and formulate information exchange strategies to support the security of the North Natuna Sea in maintaining national sovereignty. This study uses a qualitativeapproach through interviews, observations, and document studies with source triangulation. The results show that interagency coordination has been carried out through operational communication, logistical support, and the utilization of intelligence data. However, integration has not been optimal due to limitations in interoperability, the absence of continuous integrated patrols, differences in information exchange procedures, and obstacles in maritime surveillance technology. The success factors of cooperation are influenced by policy support, human resource readiness, availability of surveillance facilities, and clarity of the chain of command and control. The recommended strategies include optimizing maritime intelligence, strengthening interagency coordination forums, improving communication network security, harmonizing standard operating procedures, this strengthened synergy contributes to increased security effectiveness, state presence, and deterrence in the North Natuna Sea.